# Tutor profile: Kyle R.

## Questions

### Subject: Pre-Algebra

Simplify: (5x - 2)(x + 4)

To multiply two binomials you can use a method called FOIL to simplify. FOIL stands for first, outer, inner, and last. First: Take the first term of the left binomial and multiply it by the first term in the right binomial. 5x*x = 5x^2 Outer: Next take the first term of the left binomial and multiply it by the outer term in the right binomial. 5x*4 = 20x Inner: Take the second term in the left binomial and multiply it by the inner term in the right binomial. -2*x = -2x Last: Finally, take the second term in the left binomial and multiply it by the last term in the right binomial. -2*4 = -8 Lastly, combine all the terms together. 5x^2 + 20x - 2x - 8 20x and -2x are like terms so you can combine them 5x^2 + 18x - 8

### Subject: Basic Math

Solve 4(5 +7) - 4^2(2+9)

Remember PEMDAS(Please Excuse My Dear Aunt Sally) Parentheses, Exponents, Multiplication and Division, and Addition and Subtraction. Evaluate the problem from left to right. Start by adding the numbers in the first set of parentheses: 4*12 - 4^2(2+9) Starting from the left the next operation to do is 4^2: 4*12 - 16(2+9) Next add the numbers in the last set of parentheses: 4*12 - 16*11 From the left start by multiplying 4*12: 48 - 16*11 Next you do the next multiplication operation: 48 - 176 Finally you can subtract: 48 - 176 = -128

### Subject: Algebra

Solve for x. 10x - 7 = 11 + 4x

First observe your problem and determine what would be easiest to bring over to the other side of the equation. Normally, it's easier to bring the smaller term over first. So, lets start by subtracting 4x from both sides because what you do to one side you must do to the other. On the left side of the equation you're left with 6x - 7 and on the right side all that is left is 11. 10x - 4x - 7 = 11 + 4x - 4x 6x - 7 = 11 Next, you"ll want to bring the 7 over to the other side. On the left side 7 is being subtracted so you must add 7 to both sides. What is left is 6x = 18 6x - 7 + 7 = 11 + 7 6x = 18 Lastly, since 6 is being multiplied by x you'll need to divide 6 on both sides to get x alone. The final answer is x = 3 6x/6 = 18/6 x = 3 To check to see if you answer is right you can fill in x = 3 back into the original equation to see if both sides are equal. 10*3 - 7 = 11 + 4*3 30 - 7 = 11 + 12 23 = 23

## Contact tutor

needs and Kyle will reply soon.